Retroperitoneal Schwannoma Mimicking Uterine Myoma - Ching-Hui Chen; Cherng-Jye Jeng; Wei-Min Liu; Jenta Shen (Elsevier, 2009)
Objective: Schwannomas rarely present as pelvic masses. Most of them have been previously examined in the pelvis, vagina, retroperitoneum, and mediastinum. We report a 44-year-old woman with a pelvic mass initially diagnosed as a uterine fibroid but subsequently proven to be a retroperitoneal cellular schwannoma. Case Report: Histologic examination revealed the mass to be an Antoni A-dominated tumor that was S-100-positive, CD117-negative, and smooth muscle actin-negative. The patient underwent a total hysterectomy and removal of the tumor, and had no evidence of recurrence at 2 years' follow-up. Conclusion: In this case, the treatment of choice was complete excision of the tumor, which was considered to be curative.